Implementation of character education at SMA Negeri 3 Tondano - Pangalila, Theodorus; Sakura, Hamdan (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
Character education is a crucial element in the formation of students who are not only intellectually intelligent but also morally upright, empathetic, and socially responsible. This study aims to describe the character of students and the implementation of student character education at SMA Negeri 3 Tondano. Using a descriptive qualitative approach, data were collected through direct observation and in-depth interviews with students, teachers, and school staff. Three days of observation revealed that character values, such as discipline, responsibility, honesty, tolerance, and social care, have been fostered through daily habits, social interactions, extracurricular activities, and the school’s management environment. The Smile, Greet, Salute (3S) culture and events such as National Education Day celebrations are effective means for character building. The interview results support these findings by emphasising the consistency with which character values are applied in both the school environment and students’ daily lives. Teachers serve as role models and guide students in character development, while programs such as the Merdeka Curriculum and the Pancasila Student Profile Strengthening Project (P5) systematically strengthen the character learning process. This research suggests that character education at SMA Negeri 3 Tondano is implemented effectively, thanks to the school’s commitment, the support of its teachers, and the social environment. The findings are expected to serve as a reference in developing optimal character education strategies in senior high schools.